Anti-Cancer Properties of the Naturally Occurring Aphrodisiacs: Icariin and Its Derivatives - Tan, Hui-Li; Chan, Kok-Gan; Pusparajah, Priyia; Saokaew, Surasak; Duangjai, Acharaporn; Lee, Learn-Han; Goh, Bey-Hing (Frontiers in Pharmacology, 2016)
Epimedium (family Berberidaceae), commonly known as Horny Goat Weed or Yin Yang Huo, is commonly used as a tonic, aphrodisiac, anti-rheumatic and anti-cancer agent in traditional herbal formulations in Asian countries such as China, Japan, and Korea. The major bioactive compounds present within this plant include icariin, icaritin and icariside II. Although it is best known for its aphrodisiac properties, scientific and pharmacological studies suggest it possesses broad therapeutic capabilities, especially for enhancing reproductive function and osteoprotective, neuroprotective, cardioprotective, anti-inflammatory and immunoprotective effects. In recent years, there has been great interest in scientific investigation of the purported anti-cancer properties of icariin and its derivatives. Data from in vitro and in vivo studies suggests these compounds demonstrate anti-cancer activity against a wide range of cancer cells which occurs through various mechanisms such as apoptosis, cell cycle modulation, anti-angiogenesis, anti-metastasis and immunomodulation. Of note, they are efficient at targeting cancer stem cells and drug-resistant cancer cells. These are highly desirable properties to be emulated in the development of novel anti-cancer drugs in combatting the emergence of drug resistance and overcoming the limited efficacy of current standard treatment. This review aims to summarize the anti-cancer mechanisms of icariin and its derivatives with reference to the published literature. The currently utilized applications of icariin and its derivatives in cancer treatment are explored with reference to existing patents. Based on the data compiled, icariin and its derivatives are shown to be compounds with tremendous potential for the development of new anti-cancer drugs.